2020
DOI: 10.4081/jphr.2020.1795
|View full text |Cite
|
Sign up to set email alerts
|

Early Sexual Debut and Associated Factors among Students in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Students with early sexual debut are exposed to risky sexual behaviours. For effective intervention of early sexual debut and its consequences, determination of its magnitude and identifications of associated factors is important. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence and its associated factors of early sexual debut among students in Ethiopia. Articles were identified through databases such as PubMed, Global Health, HINARI, Google advance search, Scopus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
4
8
1
Order By: Relevance
“…The finding that shows that watching pornographic video is a risk factor for an early sexual debut is also consistent with previous studies [ 36 , 37 ]. Further, the findings have also found a linkage of adolescent use of pornography that depicts violence with sexually aggressive behaviors [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…The finding that shows that watching pornographic video is a risk factor for an early sexual debut is also consistent with previous studies [ 36 , 37 ]. Further, the findings have also found a linkage of adolescent use of pornography that depicts violence with sexually aggressive behaviors [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, those age group from 15-19 years were less likely to report sexual coercion at fi rst sexual debut compared to those aged 10-14 years. This is corroborating the results from different studies ( 27,28 ). This is attributed for young females at earlier age might lack a negotiating and convincing power to save themselves from being coerced.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that parental supervision and control on youths affects their tendency of being involved in sex. This result is in tandem with previous studies [ 43 , 50 52 ] , which confirmed a significant relationship between PM with youths not having sexual intercourse till a later date. This is an important finding because it emphasizes the necessity of PM efforts in preventing early sexual intercourse in order to reduce additional reproductive consequences.…”
Section: Discussionsupporting
confidence: 91%